Sosialisasi Persiapan Dunia Kerja: Mengasah Keterampilan Komunikasi dan Jurnalistik di SMKN 1 Martapura - Risa Dwi Ayuni (Fakultas Teknik, Universitas PGRI Banyuwangi, 2025)
This community service program aims to improve students' understanding of communication skills in the workplace, particularly in CV creation and copywriting. This activity was motivated by students' lack of understanding of the importance of a professional CV and limited insight into copywriting as a career-supporting skill. The method used in this activity included a pre-test to measure participants' initial understanding, material presentation, a hands-on practice session, and a post-test to evaluate their understanding. This activity involved 36 Visual Communication Design (DKV) students and took place in the SMKN 1 Martapura Computer Lab on November 26, 2024. The results of this activity showed a 2.65% increase in student understanding based on the post-test results compared to the pre-test. The majority of participants were able to understand the basic concepts of copywriting and effective CV preparation, although some students still needed further study. This evaluation allowed the community service team to adjust the learning approach to be more effective. In conclusion, this outreach activity successfully improved students' communication skills and is expected to provide them with the necessary skills to face the world of work. Furthermore, it is hoped that this community service program can continue to provide broader benefits to students and academics.